2019
DOI: 10.25299/jshmic.2019.vol6(1).2528
|View full text |Cite
|
Sign up to set email alerts
|

Online Reading Resources Among EFL Students: Do They Promote Reading Habit?

Abstract: The aim of this study are to describe the EFL learners’ reading habit, the factors influence of reading habit, and the impact of the use Online Reading Resources  on promoting students’ reading habit. 156 EFL learners FKIP- Islamic University of Riau involved as participants who read by using online reading resources. The study employed questionnaire, reading log, and interview intensively to collect the data.  The results of analysis data from instruments were used in this study reflected that the use of onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Meanwhile, students' behavioral reading cultures may be implicated from using the sustainable internet facility, which is recently very well-known among college students. By accessing several online reading links, such as magazines, novels, e-books, and articles (Satriani, 2019), they constructively engaged themselves in extensive reading frequently.…”
Section: Do Efl Students Gain Any Assistance From Reading Online?mentioning
confidence: 99%
“…Meanwhile, students' behavioral reading cultures may be implicated from using the sustainable internet facility, which is recently very well-known among college students. By accessing several online reading links, such as magazines, novels, e-books, and articles (Satriani, 2019), they constructively engaged themselves in extensive reading frequently.…”
Section: Do Efl Students Gain Any Assistance From Reading Online?mentioning
confidence: 99%
“…In the EFL context, having a good reading development and literacy for secondary school students means gaining more reading input-rich circumstances in which extensive reading activities are, among others, reasonably enacted to increase the students' reading attitudes and habits. Several research findings showed the need of intensifying reading habit to get better reading skills (Satriani, 2019;Erfanpour, 2013;Manan, 2017), the governments' educational agencies and school policy makers supports to extensive reading programs at schools (Firda et al, 2018), the more time allocations and uses of motivating activities to implement extensive reading programs (Endris, 2018), and the positive responses toward extensive reading programs (Salameh, 2017). Therefore, teaching the EFL subject in secondary schools has been a challenging task for secondary school teachers.…”
Section: Introductionmentioning
confidence: 99%